2015
DOI: 10.1186/s12978-015-0041-8
|View full text |Cite
|
Sign up to set email alerts
|

Birth preparedness and complication readiness among recently delivered women in chamwino district, central Tanzania: a cross sectional study

Abstract: BackgroundUnacceptably high maternal mortality rates remain a challenge in developing countries such as Tanzania. Birth Preparedness and Complication Readiness is among the key interventions that can reduce maternal mortality. Despite this, its status in Tanzania is not well documented. We assessed the practice and determinants of Birth preparedness and complication readiness among recently delivered women in Chamwino district, Central Tanzania.MethodsA community based cross-sectional study was conducted to wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

43
108
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(163 citation statements)
references
References 15 publications
43
108
12
Order By: Relevance
“…Studies conducted in Sub-Saharan Africa have reported low levels of maternal and newborn care knowledge and birth preparedness practices among women [6,1417]. In Eastern Uganda, a study revealed that only 25% of respondents had at least three components of the birth plan [10], while in rural communities of Western Uganda, only 19% had knowledge of three or more key danger signs during pregnancy, delivery, and the postpartum period [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Sub-Saharan Africa have reported low levels of maternal and newborn care knowledge and birth preparedness practices among women [6,1417]. In Eastern Uganda, a study revealed that only 25% of respondents had at least three components of the birth plan [10], while in rural communities of Western Uganda, only 19% had knowledge of three or more key danger signs during pregnancy, delivery, and the postpartum period [11].…”
Section: Introductionmentioning
confidence: 99%
“…23 Similarly, in Chamwino area, the majority of the mothers (53% of 575) were within the cohort of 21-29 years of age; although more than 70% of them completed ANC course, 69% had no knowledge of any danger sign. 15 In northern Nigeria, higher age (>30) of male partners was a better predictor of participation and support to spouse during maternity care. 19 They had better awareness on BP although not on CR, than men aged 30 and below.…”
Section: Age Of Mothers and The Husband/partnermentioning
confidence: 99%
“…Approximately 59% had knowledge on five key components of BP/CR. 15 Women who had formal education in Chamwino district, Tanzania were two times more likely to have knowledge on BP/CR than uneducated women. 15 About 67% of Malawian mothers who participated in the study had attained primary school education but were unable to identify key danger signs in pregnancy.…”
Section: Educational Status Of Women and Their Partnersmentioning
confidence: 99%
See 2 more Smart Citations